NG-Nitro-L-arginine Methyl Ester Potentiates the Effect of Aminophylline on the Isolated Rat Hemidiaphragm - Radan Stojanović; Zoran Todorović; Sonja Vuĉković; Zorica Nešić; Milica Prostran (Elsevier, 2003)
The effects of different concentrations of NG-nitro-L-arginine methyl ester (L-NAME) (0.3, 1, 3, and 10 mM), a non-selective inhibitor of NOS, on the effect of aminophylline on the isometric contraction of the isolated rat hemidiaphragm were investigated. The muscle contractions were induced by direct subtetanic electrical stimulation. Aminophylline (0.36 - 3.60 mM) produced a typical concentration-dependent increase in both parameters of the isometric contraction: tension developed (Td) and the maximum rate of rise of tension (dT/dt max). The second series of additions of aminophylline produced a more pronounced effect. L-NAME (0.3, 1, 3, and 10 mM, 30 min of incubation without stimulation) itself did not change Td and dT/dt max. However, L-NAME (1, 3, and 10 mM) produced a statistically significant potentiation of the effect of aminophylline on Td and dT/dt max.